2019
DOI: 10.1021/acs.langmuir.9b01104
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurable Microcube Assemblies at the Liquid/Air Interface: The Impact of Surface Tension on Orientation and Capillary-Force-Interaction-Driven Assembly

Abstract: The systematic investigation of the dependence of the orientation and capillary interaction of hydrophobized polystyrene microcubes at the liquid/air interface on the surface tension of the aqueous subphase is reported. By decreasing the subphase surface tension, the preferential orientation of the cubes was observed to change independent of the surfactant type from the vertex up to the edge up and finally to the face up. Concomitantly, the structure of the aggregates obtained by cube assembly was observed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 40 publications
1
11
1
Order By: Relevance
“…This observation is attributed to the change of the values of γ P 1 P 2 and θ, which alter the interface free energy. Similar observations have been reported in our previous work, where the preformed microcube assemblies at the liquid/air interface were observed to be dynamically reconfigurable by changing the surface tension of the subphase …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This observation is attributed to the change of the values of γ P 1 P 2 and θ, which alter the interface free energy. Similar observations have been reported in our previous work, where the preformed microcube assemblies at the liquid/air interface were observed to be dynamically reconfigurable by changing the surface tension of the subphase …”
Section: Resultssupporting
confidence: 91%
“…Likewise, differently oriented microcubes and assemblies with various structures, e.g., linear, square close-packed, and hexagonally close-packed were observed in our previous studies. It was also shown that the orientation of 30 μm sized microcubes and their capillary interaction at the water/air interface are governed by the wettability of the cube faces. , On the other hand, the surface tension of the subphase and size of the cubes also control the capillary interactions. Moreover, preformed aggregates of 30 μm sized microcubes at the water/air interface were shown to be dynamically reconfigurable by altering the surface tension of the stirred subphase …”
Section: Introductionmentioning
confidence: 99%
“…This hexapolar deformation drives multiple cubes to self-assemble into hexagonal or graphenelike honeycomb lattices [23]. The orientation of the particles at the interface as a function of the packing, confinement and shape has attracted many studies [22,25,24,26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, by utilizing the “Moses effect”, diamagnetic objects could be transported on the surface of even non-magnetic liquids such as water or organic liquids. , Light-induced surface flows over a photosensitive liquid substrate have also been effectively utilized for the controlled transport of floating entities. Though these methods are effective for the directed transport, all the floating entities are driven simultaneously in the same direction, inward or outward, irrespective of their properties. Manipulation strategies based on capillary interaction of floating objects , could be a potential route toward selective manipulation of the floating drops, where the mechanism depends on the curvature they create at the interface . When the adjacent interface deformations from two objects overlap, lateral capillary forces get triggered to minimize the net curvature of the interface, resulting in a relative motion of the objects .…”
Section: Introductionmentioning
confidence: 99%
“…25−27 Though these methods are effective for the directed transport, all the floating entities are driven simultaneously in the same direction, inward or outward, irrespective of their properties. Manipulation strategies based on capillary interaction of floating objects 28,29 could be a potential route toward selective manipulation of the floating drops, where the mechanism depends on the curvature they create at the interface. 30 When the adjacent interface deformations from two objects overlap, lateral capillary forces get triggered to minimize the net curvature of the interface, resulting in a relative motion of the objects.…”
Section: ■ Introductionmentioning
confidence: 99%